Impact of Leisure and Social Activities on Quality of Life Among Older Adults Over 65 in Europe – Share Data Analysis - Pluharova, Marketa; Lustigova, Michala (Calitatea Vieții, 2024)
The purpose of this article is to examine the relationship between leisure and social activities, and the quality of life of people aged 65+ in Europe. Individual data of adults over 65 in Europe were used from the SHARE database, wave 6, 2015. The relationship between 11 selected activities, divided into social, individual, and care activwities for loved ones, and quality of life (CASP-12 score) were measured. A binary logistic regression with a random effect was used. Results suggest that there is an association between active older adults in most leisure and social activities and high quality of life (CASP-12 > 39). In the multilevel analysis, 8 of 11 selected activities turned out to be protective factors for a high quality of life of elderly people in Europe. On the other hand, care activities for loved ones were not associated with a high quality of life. Not providing personal care assistance to people from the same household (OR = 1.56; CI 95%), reading books, magazines, and newspapers (OR = 1.52; CI 95%), and volunteering or charitable activities (OR = 1.36, CI 95%) were associated with higher quality of life. The level of Intraclass correlation coefficient (ICC), the percentage of the variance explained by the variability between countries for all activities, reached 17-19%. Leisure and social activities except care activities for loved ones have a positive effect on the quality of life of the elderly in Europe. The impact of these activities on the quality of life of older adults over 65 varies across Europe.